Potassium doses on fruit production and nutrition of mango (Mangifera indica L.) cv. Palmer - Lucena Calvacante, Italo Herbert; Nascimento Lima, Augusto Miguel; Alvas Carneiro, Marcio; Sales Rodriguez, Marcos; Lustosa Silva, Roberto (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2017)
Mango (Mangifera indica L.) is an economically important crop for Brazil, especially grown in São Francisco River Valley, with high demand on potassium (K) for high fruit quality and yields, but an adequate fertilizing management for K has not been defined yet and accepted by researchers as a standard. Thus, an experiment was conducted from 2013 to 2014 to evaluate the fruit production and potassium foliar concentrations of mango cv. Palmer under fertigation with five potassium chloride doses in São Francisco Valley, Brazil. The experimental design consisted of randomized blocks with treatments defined as five potassium doses (150, 225, 281, 300 and 450 g∙plant of KCl), with four replications of five plants in each parcel. The fruit production, fruit yield and number of commercial fruits, and leaf potassium concentrations of mango cv. Palmer were recorded. The fruit production and the potassium foliar concentration of mango cv. Palmer depended on potassium chloride dose applied through fertigation. Under the soil, climate and plant conditions of this study, 225 g∙plant-1 of KCl through fertigation could be recommended for the production of mango cv. Palmer.